Donating Behavior and Charity Giving on Intentions to Donate: A Literature Study - Eman Sulaiman; Refius Pradipta Setyanto; Eka Parianti (PT. Berkah Digital Teknologi, 2023)
Purpose of the study — Donation and charity is one of the cultural behaviors of the Indonesian Nation, various forms of donations and giving of charity were made and designed according to needs. This study aims to find out how the behavior of donations and what factors are contained in making donations and charities in the community and making a research model.Research method— The method used is to review the literature relating to donations and charities.Result— The results of this study produce a research model in the form of individual Behavior variables (moral core, empathy, news exposure, positive and negative performance as well as an efficient color on the emotional giving of charity), fundraising, and internet technology features that influence the behavior of donations and charity giving that have an impact Interested in donating. Intermediary of social status and sentiment and sophistationConclusion— This literature study aimed to explore the behavior of donations and charity giving in the Indonesian community and develop a research model. Through an analysis of existing literature, several key factors were identified that influence individuals' intentions to donate and engage in charitable activities.The research model developed includes individual behavior variables such as moral core, empathy, news exposure, and positive and negative performance. These variables play a significant role in shaping emotional giving and charitable behavior. Additionally, the study highlights the influence of fundraising strategies and internet technology features on donation behavior, suggesting that these factors can enhance individuals' interest in donating.Furthermore, the research model acknowledges the intermediary role of social status and sentiment, as well as sophistication, in the donation process. These factors can impact individuals' attitudes and decisions regarding charitable giving.